Ratna parīkshā - Nāhaṭā, Agaracanda, 1911-; Thakkura Pheru, fl.1291-1323; Tattvakumāra, Muni, 18th cent; Ratnaśekhara, Vācaka (Śrī Abhaya Jaina granthamālā, 1962)
Three medieval works on the appraisal of precious stones in India.